Infinitely Many Positive Solutions for a Coupled Discrete Boundary Value Problem - Liuming Li; Zhan Zhou (Discrete Dynamics in Nature and Society)
In this paper, we obtain some results for the existence of infinitely many positive solutions for a coupled discrete boundary value problem. The approach is based on variational methods.